Ogilvie's syndrome following caesarean section. (19th June 2013) - Latunde-Dada, Adeyinka Oluseun; Alleemudder, Djavid I; Webster, Daniel P
Abstract : Acute colonic pseudo-obstruction syndrome, also known as Ogilvie's syndrome, is a rare condition associated with significant morbidity and mortality. We report a case that developed very rapidly after emergency caesarean section. A 20-year-old woman underwent an emergency caesarean section for failure to progress in the first stage of labour and a healthy male infant was delivered without incident. However, soon afterwards the patient developed significant abdominal distension and pain. Ogilvie's syndrome was diagnosed following an abdominal x-ray  which revealed a gross large bowel obstruction without mechanical cause. To prevent caecal rupture, the patient underwent successful emergency colonic decompression.